Efficacy & tolerability of bisoprolol in comparison to metoprolol in Indian patients with stage-1 hypertension: multicentre, parallel group, open labelled, randomised noninferiority clinical study. (14th October 2021) - Dasbiswas, A; Reddy, P K M; Gajapati, V; Rawat, C R; Dharmadhikari, A
Abstract: Introduction: Bisoprolol & Metoprolol are selective β1 adrenergic blockers used in treatment of several diseases, including hypertension (HTN). Unlike Metoprolol, the β1-receptor selectivity of Bisoprolol does not change with increasing dose and Bisoprolol also has a longer half-life. The objective was to compare the efficacy & tolerability of Bisoprolol with Metoprolol in Indian patients with Stage-1 HTN. Method: Multicentre, parallel group, open labelled, randomised noninferiority trial was conducted at 6 cardiology centres in India (2010 – 2011). The study was approved by the institutional ethics committee at each centre and was performed in accordance with the good clinical practice guidelines and ICH-GCP. Out 218 adult patients screened, 200 patients between the age group of 18 to 65 years, with systolic blood pressure (SBP) 140–159 mm Hg or diastolic blood pressure (DBP) 90–99 mm Hg were randomly assigned to receive either Bisoprolol 5 mg once daily or Metoprolol-SR 50 mg once daily. Primary outcome measure was the responder rate (% of patients achieving BP <140/90 mm Hg throughout 24 hours) at 12 weeks. The secondary outcome measures were the percentage of patients requiring dose titration at 6 weeks, change in the SBP & DBP from baseline at 6 and 12 weeks, change in the mean night-time blood pressure from baseline at 12 weeks & global efficacy and tolerability assessment on a four-point scale. Results: 200 patients (100 each in the 2 arms, 74.5% Males, mean age of 49.55 and 53.39 in the bisoprolol and metoprolol arms respectively) were enrolled in the study. Efficacy analysis was done on 165 patients who completed the study. There was a trend towards a better 24 hr BP control rate with Bisoprolol, responder rates were 68.33% for Bisoprolol and 62.9% for Metoprolol as measured by continuous ambulatory blood pressure measurement. Also Bisoprolol was non-inferior to Metoprolol with respect to percentage of patients requiring dose titration (12.3% vs 11.6%), change in SBP (7.7% vs 7.2%) & DBP (9.6% vs 9.1%), change in mean night-time blood pressure (29.1% vs 25.3%) and reduction in heart rate (9.2% vs 6.7%). The two treatments were also similar with respect to efficacy & tolerability on Global Assessment by doctors & patients respectively. Conclusion: Bisoprolol is non-inferior to Metoprolol-SR with respect to efficacy & safety in patients of stage-1 HTN, with a trend towards better control of 24 hr BP in this non-inferiority trial. This study was conducted at a time when β-blockers were considered as first-line therapies for the management of hypertension. Our study supports the use of bisoprolol in Indian patients, based on the non-inferiority (as compared to metoprolol) and with the advantageous profile of the molecule. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): The study was supported by a research grant from Merck.